THE UTILIZATION OF AI AS A LITERACY SUPPORT TOOL TO ENHANCE ENGLISH READING SKILLS - Mufidah Yusroh; Anis Hidayati (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
This study aims to investigate the utilization of AI as a literacy support tool to enhance English reading skills. The research employed a qualitative approach using a case study design with purposive sampling. Data collection techniques included observation and interviews involving 23 respondents from the second-semester students of the Sharia Economics program. The data analysis process consisted of data collection, data reduction, conclusion drawing, and data validation. To ensure data validity, this study applied triangulation of theories and methods. The findings revealed that the use of AI made the English learning process, particularly in reading skills, more practical and engaging, as students can ask questions at any time and receive quick responses without feeling pressured. This contributed to increased interest and motivation for independent learning. However, several challenges were also identified, such as limited internet access, misunderstandings of vocabulary, occasional inaccuracies in information, and difficulties in comprehending certain answers. Some respondents also felt that they were becoming overly dependent on ChatGPT.